Faktor- Faktor yang Berhubungan dengan Kejadian Anemia pada Remaja Putri di Desa Pajar Bulan Kecamatan Semende Darat Ulu Kabupaten Muara Enim Tahun 2021 - Rahera Pembela Desi; Syarifah Isme; Eka Afrika (Universitas Batanghari Jambi, 2022)
Anemia is a condition of iron deficiency. This iron deficiency results in a decrease in the hemoglobin content in the blood. the hemoglobin level in the blood. The purpose of this study was to determine the factors associated with the incidence of anemia in adolescent girls. This study uses an analytic survey with a cross sectional research design. This research was conducted in August 2021 in Pajar Bulan village, Semende Darat Ulu District, Muara Enim Regency, South Sumatra. The study population was all Young Women with the incidence of Anemia. The sample used was 69 of the population taken using the sampling technique. Data analysis used univariate analysis (proportion) and bivariate analysis (Chi square test). The results of the analysis showed that menstrual pattern, diet, nutritional status and disease history had a significant relationship with the incidence of anemia in adolescent girls. The conclusion of this study is that there is an influence of menstrual patterns, diet, nutritional status, and disease history with the incidence of anemia in adolescent girls. Suggestions for young women can maintain and pay attention to their health, especially about anemia.